Two Distinct Nicotinic Receptors, One Pharmacologically Similar to the Vertebrate α7-Containing Receptor, Mediate Cl Currents inAplysia Neurons - Kehoe, JacSue (J Neurosci, 1998)
Ionotropic, nicotinic receptors have previously been shown to mediate both inhibitory (Cl-dependent) and excitatory (cationic) cholinergic responses in Aplysia neurons. We have used fast perfusion methods of agonist and antagonist application to reevaluate the effects on these receptors of a wide variety of cholinergic compounds, including a number of recently isolated and/or synthesized α toxins [α-conotoxin (αCTx)] fromConus snails. These toxins have been shown in previous studies to discriminate between the many types of nicotinic receptors now known to be expressed in vertebrate muscle, neuroendocrine, and neuronal cells. One of these toxins (αCTx ImI from the worm-eating snail Conus imperialis) revealed that two kinetically and pharmacologically distinct elements underlie the ACh-induced Cl-dependent response in Aplysia neurons: one element is a rapidly desensitizing current that is blocked by the toxin; the other is a slowly desensitizing current that is unaffected by the toxin. The two kinetically defined elements were also found to be differentially sensitive to different agonists. Finally, the proportion of the rapidly desensitizing element to the sustained element was found to be cell-specific. These observations led to the conclusion that two distinct nicotinic receptors mediate Cl currents inAplysia neurons. The receptor mediating the rapidly desensitizing Cl-dependent response shows a strong pharmacological resemblance to the vertebrate α-bungarotoxin-sensitive, α7-containing receptor, which is permeable to calcium and mediates a rapidly desensitizing excitatory response.